Mouse House Hunter - GERONIMO STILTON; GERONIMO STILTON (New York: Scholastic Inc., 2012)
Geronimo must sell his beloved, cozy home to save The Rodent$1 (Bs Gazette from bankruptcy after Sally Ratmousen reveals the paper is out of money. s
Keywords: The story follows the titular character, a nervous mouse journalist; making difficult sacrifices for the greater good of others